Paleoethnobotanical and experimental analysis of Geoffroea decorticans (Gill. ex Hook. & Arn.) and Sarcomphalus mistol (Griseb.) fruits in Cerro Colorado, Córdoba Province, Argentina - Saur Palmieri, Valentina (2017)
Fil: Saur Palmieri, Valentina. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Biodiversidad y Ecología; Argentina.